Nanomaterial and polymer membranes : synthesis, characterization, and applications - Saleh, Tawfik A.; Gupta, Vinod K., 1953- (Elsevier, 2016)
Nanomaterial and Polymer Membranes: Synthesis, Characterization, and Applications presents a unique collection of up-to-date polymeric nanomaterial membranes. The book offers a perfect source to document state-of-the-art developments and innovations in nanocomposite membranes, ranging from materials development and characterization of properties to membrane applications. The book discusses applications that encompass the enhancement of sorption and degradation processes and their usage for the removal of different pollutants, including heavy metals, dyes, pesticides, and other organic and inorganic pollutants from the industry.
Keywords: Nanostructured materials.; elektronické knihy; electronic books